Incidence of acute kidney injury in birth asphyxia and its correlation with severity of hypoxic ischemic encephalopathy (HIE) in newborns with perinatal asphyxia in SNCU at DR. BRAM Hospital, Raipur (CG) - Dr. Sharja Phuljhele; Dr. Shashikant Dewangan; Dr. Yogita Rathi (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Perinatal asphyxia is an important contributor of neonatal morbidity, mortality and adverse outcome in India. Due to any reason, if blood supplied through placenta is hampered, it leads to asphyxial injury. Renal involvement is frequent in perinatal asphyxia. The severity of renal involvement and adverse outcome are correlated with severity of asphyxia and HIE stage. We performed this study to determine the incidence of renal failure in birth asphyxia by estimating urine output, serum creatinine and blood urea.Aim and Objective: To study incidence of Acute Kidney Injury (AKI) in Hypoxic Ischemic Encephalopathy (HIE) and its association with severity of HIE in Newborns.Material Methods: Cross-sectional observational hospital based study was conducted over a period of six months from March 2018 to August 2018 in Special Newborn Care Unit (SNCU) of Dr. BRAM hospital, Raipur. Sarnat and Sarnat staging was used to classify HIE. Statistical analyses were performed by using SPSS21.0 software. Chi square test, P- value and likelihood ratio were calculated using appropriate tests.Result: Total 1318 newborns were admitted in SNCU during study period. 415 newborns were admitted with HIE following perinatal asphyxia. Out of these 52 (12.5%) were HIE-I cases, 242(58.3%) were HIE-II and 121(29.1%) were HIE-III. Total 70(16.9%) newborns developed AKI. None of newborn in HIE I developed AKI. 20(8.2%) newborns with HIE II developed AKI while in HIE III 50 (41.3%) newborns had AKI. There was significant correlation between HIE III and AKI (P value- 0.157).Conclusion: There is significant correlation of HIE with AKI. As severity of HIE progresses from stage-I to stage-III, there is increased risk of developing AKI.